2010
DOI: 10.1128/jvi.02387-09
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Verification of a Traceback Phenomenon in Prion Infection

Abstract: The clinicopathological phenotypes of sporadic Creutzfeldt-Jakob disease (sCJD) correlate with the allelotypes (M or V) of the polymorphic codon 129 of the human prion protein (PrP) gene and the electrophoretic mobility patterns of abnormal prion protein (PrP Sc ). Transmission of sCJD prions to mice expressing human PrP with a heterologous genotype (referred to as cross-sequence transmission) results in prolonged incubation periods. We previously reported that cross-sequence transmission can generate a new pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(112 citation statements)
references
References 27 publications
5
107
0
Order By: Relevance
“…On the basis of the findings from the present study, together with data from previous studies (2,3,5), we propose the neuropathological and biochemical criteria that may help distinguish acquired CJD caused by transmission of the V2 sCJD strain to individuals with the 129M/M genotype, here denoted acquired CJD-MMiK (the 129 M/M genotype, type i PrP Sc , and kuru plaques), from sporadic CJD. Since widespread kuru plaques have also been reported in pituitary hormone-associated iatrogenic CJD cases with the 129M/M genotype (28,29), the type of PrP Sc in these cases needs to be examined in the future.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…On the basis of the findings from the present study, together with data from previous studies (2,3,5), we propose the neuropathological and biochemical criteria that may help distinguish acquired CJD caused by transmission of the V2 sCJD strain to individuals with the 129M/M genotype, here denoted acquired CJD-MMiK (the 129 M/M genotype, type i PrP Sc , and kuru plaques), from sporadic CJD. Since widespread kuru plaques have also been reported in pituitary hormone-associated iatrogenic CJD cases with the 129M/M genotype (28,29), the type of PrP Sc in these cases needs to be examined in the future.…”
Section: Discussionmentioning
confidence: 93%
“…Type i PrP Sc (20 kDa) was reproduced in the 129M/M mice inoculated with brain homogenates from the atypical CJD cases or plaque-type dCJD. Details of the transmission properties of plaque-type dCJD, sCJD-MM1, or sCJD-VV2 have been reported previously (2,3,5). Plaque-type, plaque-type dCJD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…vCJD represents human infection with BSE from cattle (17). This phenomenon has been designated as "traceback," and traceback studies have been proven to be a useful tool to identify the origin of prions (17,(25)(26)(27). Therefore, we examined whether the transmissibility to Ki-Bov/Bov was maintained among humanized mouse-passaged vCJD prions.…”
Section: Transmission Of Vcjd Prions To Knock-in Mice Expressingmentioning
confidence: 99%
“…The current classification of sporadic Creutzfeldt-Jakob disease (sCJD), the most common human prion disease, includes six major disease phenotypes that strongly correlate at the molecular level with the genotype at the polymorphic codon 129 (methionine [M] or valine [V]) of the PRNP gene (which encodes PrP C ) and two PrP Sc profiles or types (type 1 and type 2) comprising distinctive physicochemical properties such as size after protease treatment (respectively, 21 and 19 kDa) and glycoform ratio (4,5). Recent studies in animal models have shown that phenotypic variations among sCJD phenotypes are largely maintained after transmission into genetically defined hosts, suggesting that different prion strains are the main cause of this diversity (6)(7)(8)(9)(10)(11). Although it is well established that PrP C conversion into PrP Sc involves consistent changes in the secondary structure with part of the ␣-helical structure turning into a ␤-sheet (12,13), a complete structural characterization of PrP Sc has been hampered by the propensity of the misfolded protein to form highly aggregated and detergent-insoluble polymers.…”
mentioning
confidence: 99%